Mechanical and flammability properties of hybrid recycled newspaper/sepiolite polypropylene composites [electronic resource] - Musliha Mohamed, 1988- (2013)
Thesis (Sarjana Sains (Teknologi Polimer)) - Universiti Teknologi Malaysia, 2013